Relatos de experiência em ginástica para todos: projeto de extensão universitária e a inclusão escolar - Acácio, Marcos Gabriel Schuindt [UNESP]; Venditti Junior, Rubens [UNESP]; Ugaya, Andresa de Souza [UNESP]; Ramos, Elisa Corrêa Martins [UNESP]; Souza, Luísa Parra Spagnuolo de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The "General Gymnastics at school" provides opportunities for systematic corporal practices and supervised groups of people with and without disabilities in the general exercise modalities (or gymnastics for all) and rhythmic activities. At first, this university extension project was being developed to attend local community around the campus as well as offering opportunities for Gymnastics for All (GFA) both for graduation students, interested in the content and practice of GFA, and for the general population. We´ve decided to prepare and carry out the extension project with students of State Public Education Network. The project was developed at the State School Professor Ayrton Busch, with the completion of two weekly classes (Tuesdays and Thursdays), given a class of 40 students (adolescents in the 7th year to 3rd high school series), both gender, since 2014. Through the activities, it has been possible to expand the cultural repertoire of students beyond develop the motor skills necessary for the performance of General Gymnastics/ Gymnastics for All (GG / GFA). The final product of this project results in choreographies developed jointly between scholarship and subjects, as well as presentations at Unesp and on June Festival at school. These presentations were themes and content developed in classes such as different interpretations of Gymnastics (natural, built, artistic, rhythmic, aerobics) integrating them with other forms of body expression (dance, folklore, games, theater, mime), in freeform and creativeness, highlightning body cultural aspects and individuals self experiences.

O projeto “Ginástica Geral na escola” oferece oportunidades de práticas corporais sistematizadas, supervisionadas para grupos de pessoas com ou sem deficiências nas modalidades de ginástica geral (ou ginástica para todos) e atividades rítmicas. De início, este projeto de extensão universitária estava a ser desenvolvido para atender a comunidade local em torno do campus, além de oferecer oportunidades de Ginástica para Todos (GPT) tanto para discentes do curso, interessados no conteúdo e prática de GPT, quanto para a população em geral. Optamos por realizar o projeto com alunos da Rede Pública Estadual de Ensino. O projeto foi desenvolvido na Escola Estadual Professor Ayrton Busch, com duas aulas semanais (terças e quintas-feiras), numa turma de 40 alunos (adolescentes do 7°ano do ensino fundamental a 3ª Série do ensino médio), ambos os sexos, desde 2014. Por meio das atividades propostas, tem sido possível ampliar o repertório cultural dos alunos, além desenvolver as capacidades motoras necessárias ao desempenho da Ginástica Geral/ Ginástica para Todos (GG/GPT). O produto final do projeto de extensão se consolidou em apresentações coreográficas desenvolvidas de forma conjunta entre bolsista e alunos, com apresentações na Unesp e em eventos da unidade escolar. Foram abordados temas e conteúdos desenvolvidos em aulas como as diferentes interpretações da Ginástica (natural, construída, artística, rítmica, aeróbica) integrandoas juntamente com outras formas expressão corporal (dança, folclore, jogos, teatro, mímica) de forma livre e criativa, destacando os aspectos da cultura corporal de movimento e as experiências individuais dos participantes.
Keywords: General gymnastics; UNESP; State public school; Ginástica geral; Unesp; Escola pública estadual